Falling through the cracks: Poverty and disadvantage in Australia - Duncan, Alan; Dockery, Alfred Michael; Cassells, R. (Bankwest Curtin Economics Centre, 2014)
This first report in the Bankwest Curtin Economics Centre’s new ‘Focus on the States’ series explores the level of poverty and disadvantage within Australia - how this has changed in recent times, and what differences exist among groups and throughout Australia’s states and territories Using the latest data from the ABS Survey of Income and Housing, supplemented by longitudinal and Census data, economists at BCEC have compiled a comprehensive report of the depths of income poverty and associated disadvantage that exists among Australia’s states and territories. The report is divided into two main sections – Part I examines the concept of poverty and disadvantage in the Australian context and measurement. Particular attention is paid to the depth of poverty and what groups of people are more or less likely to experience income poverty. Key dimensions of poverty and disadvantage are explored further in Part II, including the income and employment, housing, disability and locational disadvantage. Indigenous disadvantage is considered closely, as well as trends in homelessness across states and territories. Whether or not Australian governments have cultivated an environment that enables individuals and groups opportunities to succeed regardless of their background is also assessed.